Geriatric slim implants for complete denture wearers: clinical aspects and perspectives - Huard C; Bessadet M; Nicolas E; Veyrune JL (Dove Medical Press, 2013)
Cedric Huard,2 Marion Bessadet,1,2 Emmanuel Nicolas,1,2 Jean-Luc Veyrune,1,21Clermont Université, Université d'Auvergne, Centre de Recherche en Odontologie Clinique, Clermont-Ferrand, France; 2CHU Clermont-Ferrand, Service d'Odontologie, Clermont-Ferrand, FranceBackground: Advances made in prevention have helped postpone complete edentulism in older patients. However, in the elderly, the physiological state reduces patients' ability to adapt to oral rehabilitation and degrades the patient's oral condition. Consequently, elderly edentulous subjects avoid many types of foods, which can lead to substantial nutritional consequences. Complete dentures retained by implants are, currently, the treatment of reference in prosthodontic mandibular rehabilitation. Indeed, the mandibular symphysis generally tolerates implantation, even when the mandible is strongly resorbed. However, in the elderly, implant rehabilitation is compromised by the complexity of the surgical protocol and possible postoperative complications. In this context, the use of geriatric "slim implants" (GSI) offers an interesting alternative.Methods: In the present study, the surgical and prosthetic procedures for the use of GSI in a French dental hospital are presented. The objective was the stabilization of a complete mandibular denture in an elderly person, with the immediate implantation of four GSI.Results: The operating procedure was found to be less invasive, less expensive, simpler, and more efficient than the conventional procedure.Conclusion: The result strongly suggests that this protocol could be used systematically to treat complete edentulism in very elderly patients. Long-term monitoring and the evaluation of the reliability of this type of rehabilitation should be undertaken.Keywords: gerodontology, oral health, prostheses, mini-implant